2020
DOI: 10.3390/ejihpe11010001
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Personality, Emotional Intelligence, and Aggressiveness in Students: A Study Using the Big Five Personality Questionnaire for Children and Adults (BFQ-NA)

Abstract: An analysis of secondary students’ personality traits, along with a description of their emotional intelligence levels and their anger control, could be decisive when educating students to prevent anti-social behavior in academia. Very few studies on personality, emotional intelligence, and aggressive conduct exist in Spain. Some of the studies that do exist, however, only explore the relationship between emotional intelligence, personality, and prosocial behavior in secondary education students. Likewise, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
(24 reference statements)
4
13
0
1
Order By: Relevance
“…It can also be observed that students with higher scores on the ER dimension have lower scores for both manifest and relational aggression. These data are consistent with studies such as Bibi et al [ 43 ] and Antoñanzas [ 44 ], which found inverse relationships between EI and aggressive behaviours. Alvarado et al [ 45 ] and Segura et al [ 46 ] have shown that young people with a higher level of EI are less likely to show any type of aggression.…”
Section: Discussionsupporting
confidence: 93%
“…It can also be observed that students with higher scores on the ER dimension have lower scores for both manifest and relational aggression. These data are consistent with studies such as Bibi et al [ 43 ] and Antoñanzas [ 44 ], which found inverse relationships between EI and aggressive behaviours. Alvarado et al [ 45 ] and Segura et al [ 46 ] have shown that young people with a higher level of EI are less likely to show any type of aggression.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, this research demonstrated that out of five personality traits, three personality traits demonstrated a positive association with emotional intelligence, however, previously it has been found that emotional intelligence also meaningfully correlated with the Big Five personality traits (Avsec et al, 2009;Aydogmus, 2016;Boyd and Pennebaker, 2016;Obschonka et al, 2017;Antoñanzas, 2020;El Othman et al, 2020). Day et al (2005) concluded that emotional intelligence has a significant association with extraversion, openness, and agreeableness in particular, and no significant association was found between neuroticism and consciousness.…”
Section: Discussionmentioning
confidence: 48%
“…The employees with higher scores on personality traits and emotional intelligence are more related to better task performance and managing emotions with others (O' Boyle et al, 2011). Prior literature reveals a strong association between emotional intelligence and Big Five-factor personality traits (Avsec et al, 2009;Aydogmus, 2016;Alghamdi et al, 2017;Antoñanzas, 2020;El Othman et al, 2020;Feher and Vernon, 2021).…”
Section: Emotional Intelligence and Big Five Personality Traitsmentioning
confidence: 99%
See 2 more Smart Citations